Synthetic dye decolorization capacity of white rot fungus Dichomitus squalens - Eichlerová, Ivana; Homolka, Ladislav; Nerud, Frantisek (Bioresource technology, 2006)
The ability to decolorize eight chemically different synthetic dyes (Orange G, Amaranth, Orange I, Remazol Brilliant Blue R (RBBR), Cu-phthalocyanin, Poly R-478, Malachite Green and Crystal Violet) by the white rot fungus Dichomitus squalens was evaluated on agar plates. The fungus showed high decolorization capacity and was able to decolorize all dyes tested, but not to the same extent. Some of the dyes did not limit the decolorization capacity of the strain tested even at a concentration of 2g/l. The presence of the dyes in solid media reduced the mycelial growth rate of D. squalens; a positive correlation was found between the growth rate and the decolorization ability. Decolorization of Orange G and RBBR was studied also in liquid culture, where both dyes caused an enhancement of ligninolytic enzyme and overall hydrogen peroxide production and a decrease of biomass production. RBBR was removed to a higher extent than Orange G.
Keywords: Basidiomycota; Coloring Agents; biomasa; chemické látky znečišťující vodu; odpad tekutý - odstraňování; Waste Disposal, Fluid; Water Pollutants, Chemical; peroxid vodíku; čištění vody; Water Purification; barvicí látky; Hydrogen Peroxide; Biomass